Strategi Manajemen Sumber Daya Manusia untuk Meningkatkan Keunggulan Kompetitif - Muhammad Fahrul Muttaqin; Ida Rindaningsih (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
In the midst of increasingly complex globalization, organizations must continue to innovate and maximize the potential of existing resources to achieve competitive advantage. Human Resource Management (HRM) plays a strategic role in managing employees as important organizational assets. This research uses a Systematic Literature Review (SLR) approach to review various literatures that discuss the relationship between HRM strategies and achieving competitive advantage. The results of the literature analysis show that effective HRM strategies, including competency-based recruitment, employee development through training and education, fair reward systems, and the use of technology such as Human Resource Information System (HRIS), can improve organizational performance and competitiveness. In addition, transparent performance management and good internal communication are also important supporting factors. Nonetheless, challenges in implementing HRM strategies remain, such as changes in organizational culture and budget constraints, which require an adaptive approach. This research provides insights into how the right HRM strategy can contribute to the achievement of competitive advantage in the face of fast-changing global market dynamics.